Fatty Acid Composition of Baobab Seed and Its Relationship with the Genus Adansonia Taxonomy. Issue 8 (3rd August 2017) - Razafimamonjison, Gaylor; Leong Pock Tsy, Jean Michel; Randriamiarinarivo, Manitriniaina; Ramanoelina, Panja; Rasoarahona, Jean; Fawbush, Fanjaniaina; Danthu, Pascal
Abstract : Baobab seed oil contains specific fatty acids. Most of the studies on baobab fatty acids have been carried out singly and in isolation from each other, making it difficult to compare results through different species. The objective of the present study is to establish the seed fatty acid composition of each Adansonia species in order to evaluate and understand the relationships between the oil chemical compositions, the baobabs' taxonomy and, the ecological and geographical origin of each seed lot. The seed oils have been analysed using gas chromatography (GC). The oils of all baobab species contain three major fatty acids: palmitic, oleic and linoleic acids. They also contain specific fatty acids such as cyclopropenic and cyclopropanic acids, which are characteristic of the Malvaceae family seed oils. It was possible to distinguish three sections through principal components analysis using the eleven fatty acids identified by GC. The Adansonia section contains high rates of oleic acid (± 35%), the Brevitubae section is rich in palmitic acid (± 42%) and the Longitubae section contains high levels of dihydrosterulic acid (± 5%). The oil fatty acid composition, however, does not enable a definitive characterization of profiles according to species. The fatty acid composition is not significantly influenced by the geographical, soil and climate conditions of the collection sites. Abstract :